2016
DOI: 10.1016/j.arr.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

The crucial impact of lysosomes in aging and longevity

Abstract: Lysosomes are the main catabolic organelles of a cell and play a pivotal role in a plethora of cellular processes, including responses to nutrient availability and composition, stress resistance, programmed cell death, plasma membrane repair, development, and cell differentiation. In line with this pleiotropic importance for cellular and organismal life and death, lysosomal dysfunction is associated with many age-related pathologies like Parkinson’s and Alzheimer’s disease, as well as with a decline in lifespa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
136
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 202 publications
(143 citation statements)
references
References 177 publications
(225 reference statements)
7
136
0
Order By: Relevance
“…These structures reached a maximum diameter of 8–9 μm and ultrastructurally resembled the multilamellar bodies (MLBs) that we and others found in kidneys from mice with lysosomal storage diseases such as Fabry and Niemann–Pick type C (NPC1) (supplementary material, Figure S2A). In line with studies associating ageing with lysosomal impairment , aged mice also presented MLBs. As for WD feeding, subjecting mice to a high‐fat diet (HFD) resulted in MLB formation in PTECs (supplementary material, Figure S2A).…”
Section: Resultssupporting
confidence: 84%
“…These structures reached a maximum diameter of 8–9 μm and ultrastructurally resembled the multilamellar bodies (MLBs) that we and others found in kidneys from mice with lysosomal storage diseases such as Fabry and Niemann–Pick type C (NPC1) (supplementary material, Figure S2A). In line with studies associating ageing with lysosomal impairment , aged mice also presented MLBs. As for WD feeding, subjecting mice to a high‐fat diet (HFD) resulted in MLB formation in PTECs (supplementary material, Figure S2A).…”
Section: Resultssupporting
confidence: 84%
“…Although lysosomes have been mainly considered inert catabolic organelles, it is now clear that they are also crucial regulators of cell homeostasis (4). Lysosomal accumulation of uncatabolized material is a hallmark of a large number of diseases, including lysosomal storage disorders, Alzheimer's disease, Parkinson's disease, and brain aging (5)(6)(7). Moreover, it has been recently demonstrated that diverse lysosomotropic drugs accumulate within the lysosomes, affecting their function (8,9).…”
mentioning
confidence: 99%
“…The importance of pH homeostasis in aging is also apparent in humans. Human senescent cells show increased lysosomal content and increased lysosomal pH, and in age-related pathologies such as Alzheimer's and Parkinson's disease, lysosomes are dysfunctional 15 . V-ATPases are highly conserved, and Pma1 shares structural and functional similarities with the Na + K + ATPases in mammalian cells [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%